Ginseng-derived nanoparticles inhibit lung cancer cell epithelial mesenchymal transition by repressing pentose phosphate pathway activity - Yang, Lan; Jin, Wen-qi; Tang, Xiao-lei; Zhang, Shuai; Ma, Rui; Zhao, Da-qing; Sun, Li-wei (Frontiers in Oncology, 2022)
It is unclear whether ginseng-derived nanoparticles (GDNPs) can prevent tumor cell epithelial-mesenchymal transition (EMT). Here, we describe typical characteristics of GDNPs and possible underlying mechanisms for GDNP antitumor activities. First, GDNPs particle sizes and morphology were determined using nanoparticle tracking analysis (NTA) and transmission electron microscopy (TEM), respectively, while cellular uptake of PKH67-labeled GDNPs was also assessed. Next, we evaluated GDNPs antitumor effects by determining whether GDNPs inhibited proliferation and migration of five tumor cell lines derived from different cell types. The results indicated that GDNPs most significantly inhibited proliferation and migration of lung cancer-derived tumor cells (A549, NCI-H1299). Moreover, GDNPs treatment also inhibited cell migration, invasion, clonal formation, and adhesion tube formation ability and reduced expression of EMT-related markers in A549 and NCI-H1299 cells in a dose-dependent manner. Meanwhile, Kaplan-Meier analysis of microarray data revealed that high-level thymidine phosphorylase (TP) production, which is associated with poor lung cancer prognosis, was inhibited by GDNPs treatment, as reflected by decreased secretion of overexpressed TP and downregulation of TP mRNA-level expression. In addition, proteomic analysis results indicated that GDNPs affected pentose phosphate pathway (PPP) activity, with ELISA results confirming that GDNPs significantly reduced levels of PPP metabolic intermediates. Results of this study also demonstrated that GDNPs-induced downregulation of TP expression led to PPP pathway inhibition and repression of lung cancer cell metastasis, warranting further studies of nano-drugs as a new and promising class of anti-cancer drugs.